Rheumatic Manifestations of Sarcoidosis - Julia Day; Philip D. H. Hamann (Diagnostics)
Sarcoidosis is a multisystem granulomatous inflammatory disorder, of unknown aetiology, which causes a wide spectrum of clinical phenotypes. It can present at any age, most commonly between 20 and 60 years, with a roughly equal sex distribution. Diagnosis is often delayed due to multiple diagnostic mimics, particularly joint disease. Common presenting features include pulmonary disease, with bilateral hilar lymphadenopathy and pulmonary infiltrates, cutaneous lesions, and ocular disease. Musculoskeletal manifestations are reported in 10–40% of patients with sarcoidosis and include bone lesions, acute arthritis, chronic arthritis, axial disease, dactylitis, and sarcoid myopathy, which are explored in detail in this review article. Diagnosis is confirmed through histological evidence of non-caseating granuloma on tissue biopsy. Newer imaging modalities, including 18FFDG PET/CT, can help identify the extent of musculoskeletal involvement, and biomarkers can provide weight to a diagnosis, but there is no single biomarker with prognostic value for disease monitoring. The mainstay of treatment remains corticosteroids, followed by disease-modifying antirheumatic drugs such as methotrexate and antimalarials. More recently, biologic treatments have been used successfully in the treatment of sarcoidosis with rheumatic involvement.